2021
DOI: 10.3390/plants10040704
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Size and Light Use Efficiency Explain Growth Differences between Lettuce and Mizuna in Vertical Farms

Abstract: Vertical farming is increasingly popular due to high yields obtained from a small land area. However, the energy cost associated with lighting of vertical farms is high. To reduce this cost, more energy efficient (biomass/energy use) crops are required. To understand how efficiently crops use light energy to produce biomass, we determined the morphological and physiological differences between mizuna (Brassica rapa var. japonica) and lettuce (Lactuca sativa ‘Green Salad Bowl’). To do so, we measured the projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
2
15
0
1
Order By: Relevance
“…It has decreased significantly only in response to red light proportion fall from 50% to 37% (treatments 1 and 2, respectively). Both high Φ PSII and high chlorophyll content may increase the ETR, CO 2 assimilation rate, and potentially the growth rate of plants [ 54 ], as it was also observed in treatment 5 in our experiment.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It has decreased significantly only in response to red light proportion fall from 50% to 37% (treatments 1 and 2, respectively). Both high Φ PSII and high chlorophyll content may increase the ETR, CO 2 assimilation rate, and potentially the growth rate of plants [ 54 ], as it was also observed in treatment 5 in our experiment.…”
Section: Discussionsupporting
confidence: 72%
“…It shows that some disorders could occur in the photosynthetic apparatus. To understand how different lighting strategies to influence plant growth, it is important to determine ΦPSII since this partly determines how efficiently they use the absorbed light for photosynthesis and biomass production [ 54 ]. Decreased ratio of R 660 in the spectrum of incident light resulted in the increased quantum yield of photosystem II.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PPFD increased Pn (Figure 2) but reduced pLUE (Table 3). Jayalath and van Iersel [10] also reported that a high PPFD decreased the RUE by reducing the quantum yield of photosystem II. In Experiment 1, the RUE of plants in W300 was the highest among the three treatments.…”
Section: Experiments 1: Ppfd Effectmentioning
confidence: 91%
“…Radiation-use efficiency (RUE) is a good index for measuring radiation utilization by plants [8,9] and an important quantifier of crop production in relation to photosynthesis, as it combines both the amount of radiation captured by the crop and the production of dry matter. PPFD can influence the RUE of plants by affecting the photosynthetic rate [10], stomatal behavior [11,12], photosynthate distribution [13,14], and chlorophyll content [15,16]. RUE is the highest under a PPFD of 200 µmol m −2 s −1 in lettuce and under a PPFD of 250 µmol m −2 s −1 in basil [17].…”
Section: Introductionmentioning
confidence: 99%
“…Plant phenotyping is a set of methodologies and protocols used to study plant performance, growth, architecture, and composition at different scales of organization, from organs to canopies, and it elucidates the plant trait dynamics in a non-destructive and non-invasive manner [5,14,[19][20][21]. Having great potential for application to commercial PFALs [22], imagebased studies in PFALs have been conducted, including quantifying the projected leaf area (value measured by 2D camera images captured from above the plant canopy or seedling trays) of the plant canopy [15,[23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%